2022
DOI: 10.1080/00918369.2022.2043130
|View full text |Cite
|
Sign up to set email alerts
|

Stretched Kinship: Parental Rejection and Acceptance of Queer Youth in Chinese Families

Abstract: Kinship has been the primary concern among young queer people in today's China and other parts of Asia under the strong and ongoing familism, who often find it challenging to come out and negotiate their sexuality with their parental family. This paper adopts the concept of stretched kinship to critically analyze the digital videos released by PFLAG China (Parents and Friends of Lesbians and Gays in China) from 2015 to 2020, focusing on the experiences of the parents in their responses to young people's coming… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As explored earlier in this paper, my participants accounted for education and career as enabling them to stand up against the filial obligation of 'getting married and having kids'. In the meantime, a new queer normativity emerged from their practices as less rigid expression of neo-familism (Wei, 2022;Yan, 2018), reconfiguring the passive and obedient form of filial piety into active maintenance of a 'good relationship' and intimacy with their family (Song, 2022). However, it is often neglected that queer girls and young women have to take on the responsibility of educating parents as a form of queer labour to manage family relationship (Huang and Brouwer, 2018) and gain recognition by using what they have learned from social media and particularly digital feminisms.…”
Section: Concluding Marks: Queering a Filial Girlhood?mentioning
confidence: 99%
“…As explored earlier in this paper, my participants accounted for education and career as enabling them to stand up against the filial obligation of 'getting married and having kids'. In the meantime, a new queer normativity emerged from their practices as less rigid expression of neo-familism (Wei, 2022;Yan, 2018), reconfiguring the passive and obedient form of filial piety into active maintenance of a 'good relationship' and intimacy with their family (Song, 2022). However, it is often neglected that queer girls and young women have to take on the responsibility of educating parents as a form of queer labour to manage family relationship (Huang and Brouwer, 2018) and gain recognition by using what they have learned from social media and particularly digital feminisms.…”
Section: Concluding Marks: Queering a Filial Girlhood?mentioning
confidence: 99%
“…Another group of homosexuals choose to come clean with their families directly about their sexual orientation, and such behavior often leads to violent family conflicts, such as arguments and even beatings. Some parents may choose to cut off their parent-child relationship with their children and refuse to interact with each other [25].…”
Section: The Intensification Of Social Problems and Conflictsmentioning
confidence: 99%
“…Meanwhile, the emotional and economic supports from the original family still play an important role, and today's young queer people often maintain their family connections while transitioning towards freedom and autonomy (Holdsworth, 2009;Krzaklewska, 2019;Wei, 2020). Recent studies in Asia and North America have also shown that young queer people's socioeconomic background is directly linked to how their families respond to their identity disclosure (Schmitz and Tyler, 2018c;Wei, 2022).…”
mentioning
confidence: 99%
“…Extending and deviating from the concept of 'chosen family', one of us (Wei, 2020(Wei, , 2022 has developed the concept of 'stretched kinship' to understand the relationship between young queer people and their families of origin. We argue that queer people's mobility for education and employment often leaves their family relationships physically and emotionally detached yet still in a resilient connection, as young people negotiate their sexuality across a distance with their family (2020: 33).…”
mentioning
confidence: 99%